Responsabilidade social nas ações de extensão do Programa Iniciativas Negras: trocando Experiências - Silva, Elieny do Nascimento (2012)
In recent decades, globalization has changed the business environment, significantly influencing the management of business, a factor that contributes to the incorporation of social responsibility in institutions. In this regard, the social question has become more evident, showing even more social problems of nations. Because being the university a multidimensional space, the study of social responsibility in the context of traffic makes it possible to include the citizenship issue in higher education, providing for discussions about the strengthening of social and individual rights, equality and justice as supreme values of a democratic society. This survey found the University Social Responsibility from the perspective of the extent the actions of Black Outreach Program Initiatives: sharing experiences from the perspective of Course IN (2011), its coverage nationwide and its impacts in the region of Cariri. In order to achieve the outlined purposes an exploratory study was conducted. The field and the research population were fellows of the Third Course IN (2011) and the participants in the Cariri. The following data collection techniques used were: Application forms of scholarship recipients, questionnaires and field diary, which are instruments of support needed for data collection. The collected data were categorized into two major groups: those that evaluate the impacts of black outreach program initiatives through courses in Event III (2011), at the national level, those that evaluate the impact of that program from the participants' perceptions from the region of Cariri. Data analysis was based on a comprehensive approach, which values the qualitative data analysis. For the interpretation of qualitative data from this study we used the method of interpretation of meanings. The analysis shows the impacts of Course IN (2011). These impacts caused by this action denoted the social responsibility of the University Extension Program Initiatives Black: exchanging experiences.